Kinetics Study Addition Reaction for Methyleugenol with Formic Acid to Produce The Methyleugenol Formic Ester as Intermediate Compound of Hypertension Drug - Fadhilah, Nabila Nur; Nugraha, Asep Wahyu; Purba, Jamalum; Dibyanti, Ratu Evina (Universitas Negeri Medan, 2025)
The methyl eugenol formic ester is the intermediate formation of the 1-(3,4-dimethoxy phenyl)-2-amino-2-cyano propane compound, a hypertension drug. This study aimed to find the value of the reaction order and study the mechanism of an addition reaction of methyl eugenol with formic acid to produce the methyl eugenol formic ester. Gas chromatography analysis of the residual methyl eugenol determines the reaction order. There are two dominant products in the synthesis of methyl eugenol formic ester, resulting in the formation reaction of methyl eugenol formic predictable in a two-way reaction mechanism. The determination of the energy of the reactants, products, and transition compounds in the formation reaction of methyl eugenol formic ester compound prescribed through computational studies using NWChem 6.0 and visualization using Jmol. The results of the analysis of the data obtained several conclusions: The value of the reaction ordered for methyl eugenol with formic acid is the first order. Based on the computational result shows that the enthalpy change for the reaction product is ΔH(1) = -47,810 KJ/mol and ΔH(2) = -60,545 KJ/mol. The activation energy for both transition compounds is Ea(1) = 163,1937 KJ/mol and Ea(2) = 370,3477 KJ/mol. This fact indicates that the formation of methyl eugenol formic ester compound using the method (1) was more likely than (2). The prediction is based on the determination of Ea with the computational chemistry following the experimental result, which shows the product of (1) more than the product of (2).